Symbol

# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Solve the equation
Graph
$y = 4 \left ( x - 2 \right ) ^ { 2 }$
$y = 12$
$x$Intercept
$\left ( 2 , 0 \right )$
$y$Intercept
$\left ( 0 , 16 \right )$
Minimum
$\left ( 2 , 0 \right )$
Standard form
$y = 4 \left ( x - 2 \right ) ^ { 2 }$
$4 \left( x-2 \right) ^{ 2 } = 12$
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = 2 - \sqrt{ 3 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = 12$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 16 } = 12$
$4 x ^ { 2 } - 16 x + 16 = \color{#FF6800}{ 12 }$
 Move the expression to the left side and change the symbol 
$4 x ^ { 2 } - 16 x + 16 \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 16 } \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
 Subtract $12$ from $16$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 4 } = 0$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 3 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 3 }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \pm \sqrt{ \color{#FF6800}{ 3 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \pm \sqrt{ \color{#FF6800}{ 3 } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 3 } } \end{array}$
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = 2 - \sqrt{ 3 } \end{array}$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = 12$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 16 } = 12$
$4 x ^ { 2 } - 16 x + 16 = \color{#FF6800}{ 12 }$
 Move the expression to the left side and change the symbol 
$4 x ^ { 2 } - 16 x + 16 \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 16 } \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
 Subtract $12$ from $16$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 4 } = 0$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = 0$
 Bind the expressions with the common factor $4$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 0$
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 0 }$
 Divide both sides by $4$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 4 \right ) \pm \sqrt{ \left ( - 4 \right ) ^ { 2 } - 4 \times 1 \times 1 } } { 2 \times 1 }$
 Simplify Minus 
$x = \dfrac { 4 \pm \sqrt{ \left ( - 4 \right ) ^ { 2 } - 4 \times 1 \times 1 } } { 2 \times 1 }$
$x = \dfrac { 4 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 1 } } { 2 \times 1 }$
 Remove negative signs because negative numbers raised to even powers are positive 
$x = \dfrac { 4 \pm \sqrt{ 4 ^ { 2 } - 4 \times 1 \times 1 } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm \sqrt{ 4 ^ { 2 } - 4 \times 1 \times 1 } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm \sqrt{ 12 } } { 2 \times 1 } }$
$x = \dfrac { 4 \pm \sqrt{ \color{#FF6800}{ 12 } } } { 2 \times 1 }$
 Organize the part that can be taken out of the radical sign inside the square root symbol 
$x = \dfrac { 4 \pm \color{#FF6800}{ 2 } \sqrt{ \color{#FF6800}{ 3 } } } { 2 \times 1 }$
$x = \dfrac { 4 \pm 2 \sqrt{ 3 } } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 4 \pm 2 \sqrt{ 3 } } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 \pm 2 \sqrt{ 3 } } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 + 2 \sqrt{ 3 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 4 + 2 \sqrt{ 3 } } { 2 } } \\ x = \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 2 + \sqrt{ 3 } } { 1 } } \\ x = \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } \end{array}$
$\begin{array} {l} x = \dfrac { 2 + \sqrt{ 3 } } { \color{#FF6800}{ 1 } } \\ x = \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } \end{array}$
 If the denominator is 1, the denominator can be removed 
$\begin{array} {l} x = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 3 } } \\ x = \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } \end{array}$
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = \color{#FF6800}{ \dfrac { 4 - 2 \sqrt{ 3 } } { 2 } } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = \color{#FF6800}{ \dfrac { 2 - \sqrt{ 3 } } { 1 } } \end{array}$
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = \dfrac { 2 - \sqrt{ 3 } } { \color{#FF6800}{ 1 } } \end{array}$
 If the denominator is 1, the denominator can be removed 
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 3 } } \end{array}$
 2 real roots 
Find the number of solutions
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = 12$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 16 } = 12$
$4 x ^ { 2 } - 16 x + 16 = \color{#FF6800}{ 12 }$
 Move the expression to the left side and change the symbol 
$4 x ^ { 2 } - 16 x + 16 \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 16 } \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
 Subtract $12$ from $16$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 4 } = 0$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 16 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 16 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 4 \times 4$
 Remove negative signs because negative numbers raised to even powers are positive 
$D = 16 ^ { 2 } - 4 \times 4 \times 4$
$D = \color{#FF6800}{ 16 } ^ { \color{#FF6800}{ 2 } } - 4 \times 4 \times 4$
 Calculate power 
$D = \color{#FF6800}{ 256 } - 4 \times 4 \times 4$
$D = 256 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
 Multiply the numbers 
$D = 256 \color{#FF6800}{ - } \color{#FF6800}{ 64 }$
$D = \color{#FF6800}{ 256 } \color{#FF6800}{ - } \color{#FF6800}{ 64 }$
 Subtract $64$ from $256$
$D = \color{#FF6800}{ 192 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 192 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = 4 , \alpha \beta = 1$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = 12$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 16 } = 12$
$4 x ^ { 2 } - 16 x + 16 = \color{#FF6800}{ 12 }$
 Move the expression to the left side and change the symbol 
$4 x ^ { 2 } - 16 x + 16 \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 16 } \color{#FF6800}{ - } \color{#FF6800}{ 12 } = 0$
 Subtract $12$ from $16$
$4 x ^ { 2 } - 16 x + \color{#FF6800}{ 4 } = 0$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 16 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 16 } { 4 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 4 } { 4 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 16 } { 4 } } , \alpha \beta = \dfrac { 4 } { 4 }$
 Solve the sign of a fraction with a negative sign 
$\alpha + \beta = \color{#FF6800}{ \dfrac { 16 } { 4 } } , \alpha \beta = \dfrac { 4 } { 4 }$
$\alpha + \beta = \color{#FF6800}{ \dfrac { 16 } { 4 } } , \alpha \beta = \dfrac { 4 } { 4 }$
 Reduce the fraction 
$\alpha + \beta = \color{#FF6800}{ 4 } , \alpha \beta = \dfrac { 4 } { 4 }$
$\alpha + \beta = 4 , \alpha \beta = \color{#FF6800}{ \dfrac { 4 } { 4 } }$
 Reduce the fraction 
$\alpha + \beta = 4 , \alpha \beta = \color{#FF6800}{ 1 }$
$\begin{array} {l} x = 2 + \sqrt{ 3 } \\ x = 2 - \sqrt{ 3 } \end{array}$
Solve the fractional equation
$\color{#FF6800}{ 4 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 12 }$
 Solve quadratic equations using the square root 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 3 } } \end{array}$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture